Underground Economy And Taxation Of Prostitution (Literature Study In Indonesia) - Al Hazmi, Raldin Alif (WIM Solusi Prima, 2024)
Prostitution is actually an undergorund economy that is difficult to detect, because every commercial sex worker in this business is difficult to distinguish from ordinary people in general. In terms of taxation, tax is designed not to recognise assets obtained from legal activities, and from illegal activities, no matter whether the income is obtained from corruption, prostitution, human trafficking, illegal arms trade and even narcotics. As long as it is known that there is an increase in income or enjoyment, the state has the right to collect taxes. However, the relationship between prostitution and taxes is very sensitive. Prostitution business has a huge potential. Exploring the potential of this business if done massively will increase tax revenue significantly, but there is a trade off that DJP must face. In this case, DJP must also use the moral point of view prevailing in society. Taxing something illegal and immoral will indirectly give an opinion to the public that the state legalises the activity.